Early Local Therapy for the Primary Site in De Novo Stage IV Breast Cancer: Results of a Randomized Clinical Trial (EA2108). Issue 9 (20th March 2022) - Khan, Seema A.; Zhao, Fengmin; Goldstein, Lori J.; Cella, David; Basik, Mark; Golshan, Mehra; Julian, Thomas B.; Pockaj, Barbara A.; Lee, Christine A.; Razaq, Wajeeha; Sparano, Joseph A.; Babiera, Gildy V.; et al.
Abstract : PURPOSE: Distant metastases are present in 6% or more of patients with newly diagnosed breast cancer. In this context, locoregional therapy for the intact primary tumor has been hypothesized to improve overall survival (OS), but clinical trials have reported conflicting results. METHODS: Women presenting with metastatic breast cancer and an intact primary tumor received systemic therapy for 4-8 months; if no disease progression occurred, they were randomly assigned to locoregional therapy for the primary site (surgery and radiotherapy per standards for nonmetastatic disease) or continuing sysmetic therapy. The primary end point was OS; locoregional control and quality of life were secondary end points. The trial design provided 85% power to detect a 19.3% absolute difference in the 3-year OS rate in randomly assigned patients. The stratified log-rank test and Cox proportional hazards model were used to compare OS between arms. Cumulative incidence of locoregional progression was compared using Gray's test. Quality-of-life assessment used standard instruments. RESULTS: Of 390 participants enrolled, 256 were randomly assigned: 131 to continued systemic therapy and 125 to early locoregional therapy. The 3-year OS was 67.9% without and 68.4% with early locoregional therapy (hazard ratio = 1.11; 90% CI, 0.82 to 1.52; P = .57). The median OS was 53.1 months (95% CI, 47.9 to not estimable) in the systemic therapy arm and 54.9 months (95% CI, 46.7 to not estimable) in the locoregional therapy arm. Locoregional progression was less frequent in those randomly assigned to locoregional therapy (3-year rate: 16.3% v 39.8%; P < .001). Quality-of-life measures were largely similar between arms. CONCLUSION: Early locoregional therapy for the primary site did not improve survival in patients presenting with metastatic breast cancer. Although it was associated with improved locoregional control, this had no overall impact on quality of life. Abstract :